2023
DOI: 10.1097/hjh.0000000000003499
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary factors and hypertension risk in West Africa: a systematic review and meta-analysis of observational studies

Abstract: Background: Contrary to North America and Europe, the prevalence of hypertension is rising in West Africa. Although diet is implicated as a contributor to this trend, nutritional guidelines in West Africa are not tailored to address this concern. This study aimed to address this limitation by investigating dietary factors common to West Africa and evaluating their association with hypertension. Methods: PubMed, Scopus, Web of Science, and Medline were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 106 publications
1
17
0
Order By: Relevance
“…Furthermore, the Bland-Altman analysis was used to assess the level of agreement between the FFQ and 24DR ( S3 Table ). Fig 3A-F presents the Bland-Altman plots for the 3 healthy food groups of the DASH diet (e.g., fruits, vegetables, and nuts and seeds) [42] and 3 less healthy food groups/items identified by our recent meta-analysis of foods associated with hypertension in West African countries, including Nigeria [12] (e.g., salt, fried/fast foods, and fats and oils). The plots for the remaining food groups are provided in supplementary materials ( S1 Fig).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the Bland-Altman analysis was used to assess the level of agreement between the FFQ and 24DR ( S3 Table ). Fig 3A-F presents the Bland-Altman plots for the 3 healthy food groups of the DASH diet (e.g., fruits, vegetables, and nuts and seeds) [42] and 3 less healthy food groups/items identified by our recent meta-analysis of foods associated with hypertension in West African countries, including Nigeria [12] (e.g., salt, fried/fast foods, and fats and oils). The plots for the remaining food groups are provided in supplementary materials ( S1 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…The validity and reproducibility of our study data provide compelling evidence to further investigate the implementation and use of our novel FFQ as a practical clinical tool to screen and evaluate patient-mediated dietary risk for hypertension. The FFQ was able to rank intakes in food groups associated with hypertension [11, 12], including fruits, vegetables, grains, dairy, salt and fats and oil-based foods (soups and stew), to a similar degree of accuracy as 24DR, but was able to be completed in < 20 minutes. The results indicate that the FFQ can identify patients with high-risk dietary patterns who may benefit from prioritised education and support around dietary modification for blood pressure management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, mixing fruit juice with sugar-sweetened beverages (up to ∼23%) moderately increases blood pressure while removal of sugar-sweetened beverages decreases blood pressure irrespective of the presence or absence of hypertension (Liu et al, 2023). Consistently, another observational study from West African countries reported that higher consumption of red meat, dietary fat, salt, junk food, and alcohol are linked with increased blood pressure and hypertension while higher consumption of fruit and vegetables was protective against hypertension (Batubo et al, 2023).…”
mentioning
confidence: 80%